Storytelling on the Borders - Holmes-Rodman, Paula (Ars Medica, 2025)
What is the last story you would tell? Scribe posed, pen in hand, questions open, cardboard backed lined paper ready to go, clock ticking. Hers, not mine. I had time. I had asked before. But only in the scant week before her medically assisted death at 3pm, July 4th, did Mom want to talk about her life. To get it down. We spoke for just for an hour each evening, or maybe a bit more to squeeze in a tale’s ending. She tired so easily, and her words were cough-punctuated and whiskey-watered. I came to think of our narrative cocktail hour as “Scotch and Stories.” Scotch for her - always - and on this occasion, for me too. Shepherding the dying, and dying itself, is ghostly, thirsty work. And the stories were for me - upon my request, but in her order. It was con/scription of the highest rank. She was a reluctant storyteller. I was a willing recruit, desperate to learn even the littlest of the yet unlearned lessons, hear even the tiniest fragment of a yet unheard story. An ethnographer by trade and a literary stringsaver by heart, I knew the value of a good story, especially one gathered on the borders between two lands, two peoples, two times.